Pengaruh Pendekatan Permainan dalam Kartu Pinmat Math Hero terhadap Pemahaman Matematika di Tingkat Sekolah Dasar - Mohammad, Wily; Maulidiyah, Nabilla Ryca (Indonesian Journal Publisher, 2023)
This qualitative research investigates the use of the Math Hero Flashcards in elementary school children's mathematics education. Math Hero Flashcards are specially designed learning tools aimed at enhancing mathematical understanding, accuracy, and mastery of arithmetic operations for numbers 1-10 through interactive games. The study involves direct observation, interviews, and interactive play with children with the aim of understanding the effects of Math Hero Flashcards on children's mathematical understanding, learning motivation, and interest. The results of the research indicate that the use of Math Hero Flashcards enhances elementary school children's mathematical understanding, fosters motivation for learning, and creates a more enjoyable learning experience. However, some interview participants mentioned that they had found alternatives in the form of math game apps on their phones. Therefore, this research underscores the need for integration between physical learning tools like Math Hero Flashcards and learning technology to achieve holistic and engaging mathematics education for children.